Architectural influence of polymer brush-modified tri-compartmental anisotropic particles in stabilizing pickering emulsion - Pradhan S.S.; Upadhyay A.; Shrivastava S.; Singh A.; Saha S. (My University, 2025)
We aimed to create tri-compartmental polymeric particles (TPs), with selective areas conjugated with hydrophilic patches, to produce an array of amphiphilic particles with various architectures. Briefly, the electrohydrodynamic co-jetting technique (EHDC) was employed to produce 4 sets of TPs comprising PLA (polylactide) in one/two compartments and a blend of PLA and a macro-initiator at a ratio of 90/10 in other compartments (s). Upon grafting a hydrophilic polymer brush (poly(2-dimethyl amino ethyl methacrylate) (polyDMAEMA)) onto the surface of macroinitiator (10 wt%) containing compartment using Surface Initiated Atom Transfer Radical Polymerization (SIATRP), particles were expected to become amphiphilic. By locating the macroinitiator in various compartments (TBP 1–4), an array of amphiphilic particles with various architectures was created. This study allowed us to produce a repertoire of anisotropic particles with varying amphiphilicity for investigating their role as Pickering emulsion stabilizers beyond Janus geometry. The relative performance of the brush-modified TPs (TBPs) in stabilizing octanol/water-based emulsion was explained with the aid of their HLB balance, interfacial tension, location of the macroinitiator, and the macroinitiator content/grafting density. The particles having a maximum area of hydrophilic lobes confined to one hemisphere were found to prolong the emulsion stability for the maximum time (∼8 days), thus considered the most efficient one. In addition to polyDMAEMA, strongly hydrophilic poly(ethylene glycol methyl ether methacrylate) (polyEGMA) brushes were also grafted onto TPs to enhance their hydrophilicity, which ultimately yielded an emulsion with prolonged stability (∼11 days). © 2025 Elsevier Ltd